Fish mortality associated to volcanic eruptions in the Canary Islands - Caballero, María José; Perez-Torrado, Francisco José; Velázquez-Wallraf, Alicia; Betancor, Mónica Beatriz; Fernández, Antonio; Castro-Alonso, Ayoze (Frontiers in Marine Science, 2023)
The Canary Islands are an active volcanic archipelago. In the last decade this volcanic activity has occurred twice in the youngest and westernmost island of the archipelago: the submarine eruption on the island of El Hierro, in 2011-12, and the terrestrial eruption of the island of La Palma, in 2021. During the underwater volcanic eruption of El Hierro, a notable high and early mortality of fishes was registered. 70 fish specimens of different species were necropsied. In most of them, generalized congestion in the gills, liver, spleen, kidney, heart and rete mirabile of the swim bladder was observed. Some specimens also presented exophthalmia, gastric eversion, ocular haemorrhages, over-inflation of swim bladder and gas bubbles mainly on the skin and cornea. The recent eruption of La Palma volcano was terrestrial, characterized by the emission of large amounts of lava flows (mainly a’a in morphology) and pyroclastic deposits (mainly ash in size) both, on land and sea. Lava flowed initially on land but, eventually, it arrived at the sea water and produced the formation of lava deltas in the coastline of La Palma. This event was also associated with an increase in fish mortality but slighter than the one described for El Hierro. 14 fish specimens of different species, from locations near to the lava deltas, were necropsied. The presence of ash particles in opercula/oral cavities and gills was observed. In addition, several fishes presented an intense intestinal impaction composed of volcanic material including ashes and hyaloclastites fragments. To our best knowledge this study describes, for the first time, pathological findings in dead fishes associated with two different styles of recent volcanic eruptions in the Canary Islands.